Ethylenediamine and Pentaethylene Hexamine Modified Bamboo Sawdust by Radiation Grafting and Their Adsorption Behavior for Phosphate - Jifu Du; Houhua Xiong; Zhen Dong; Xin Yang; Long Zhao; Jun Yang (Applied Sciences, 2021)
Phosphate is an important component for the growth of plants and microorganisms; however, excess phosphate causes serious eutrophication in natural waters. New potential low-loss adsorbents from natural biomass for phosphate removal are desired. Bamboo is one of the most abundant renewable cellulose resources; however, the pure bamboo cellulose is poor to adsorb phosphate. To enhance the adsorption capacity, in this work, bamboo sawdust (BS) was chemically modified by two kinds of amines. First, glycidyl methacrylate (GMA) was grafted on BS using radiation induced graft polymerization. Then, the GMA-grafted BS was further modified by a ring-opening reaction with amines, including ethylenediamine (EDA) and pentaethylene hexamine (PEHA). The amine groups were then quaternized to prepare the BS-GMA-EDA-Q and BS-GMA-PEHA-Q adsorbents. The adsorbents were characterized by FTIR, SEM, TG, and XPS analysis. The adsorption performances of the adsorbents for phosphate were evaluated through batch experiments. The adsorption by BS-GMA-EDA-Q and BS-GMA-PEHA-Q both well obeyed the pseudo-second-order kinetic model and the Langmuir isotherm model, indicating that the adsorption process was chemical monomolecular layer adsorption. The maximum adsorption capacities for BS-GMA-EDA-Q and BS-GMA-PEHA-Q calculated by the Langmuir model were 85.25 and 152.21 mg/g, respectively. A total of 1 mol/L HCl was used to elute the saturated adsorbents. A negligible decrease in adsorption capacity was found after five adsorption–desorption cycles.